Achyranthes bidentata polysaccharides attenuate hypoxic renal injury by reducing neutrophil extracellular traps and suppressing the NLRP3/ASC/caspase-1 pathway: a preliminary study - Li, Kai; Fang, JingWei; Xie, GuangMin; Wei, FangNing; Lv, JunYing (Frontiers in Pharmacology, 2025)
AimThe aim of this study was to investigate whether Achyranthes bidentata polysaccharides (ABPSs) alleviate hypoxic renal injury (HRI) and the possible mechanism.MethodsThe HRI rat model was established using a hypobaric hypoxia chamber. Rats were divided into a control group, a hypoxia group, low-dose ABPS (ABPL) group, a high-dose ABPS (ABPH) group, a DNase I-positive control group, and an NLRP3 agonist nigericin sodium salt (NSS) group. Blood serum components relevant to neutrophil extracellular traps (NETs), including cell-free DNA (cf-DNA), myeloperoxidase-DNA (MPO-DNA), neutrophil elastase-DNA (NE-DNA), citrullinated histone 3 (cit-H3), blood urea nitrogen (BUN), serum creatinine (Scr), cystatin C (CysC), neutrophil gelatinase-associated lipocalin (NGAL), and kidney injury molecule-1 (KIM-1), were analyzed. NOD-like receptor protein 3 (NLRP3) pathway proteins, MPO, NE, cit-H3, and reactive oxygen species (ROS) in renal tissues were analyzed by multiplex fluorescence immunohistochemistry. MPO and cit-H3 in renal tissues were analyzed via Western blot. Oxidative stress markers such as malondialdehyde (MDA) and superoxide dismutase (SOD) were analyzed using the thiobarbituric acid (TBA) assay.ResultsThe results demonstrated that ABPSs exerted protective effects against hypoxic renal injury. First, ABPSs significantly reduced the levels of cf-DNA, MPO-DNA, and cit-H3, with efficacy comparable to that of DNase I. Second, ABPSs markedly suppressed the activation of the NLRP3 inflammasome pathway by degrading NETs, as evidenced by reduced protein expression of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC), and caspase-1, accompanied by significant decreases in interleukin 1β (IL-1β) and IL-18. Furthermore, ABPSs effectively alleviated oxidative stress by reducing MDA, enhancing SOD activity, and attenuating ROS. Finally, these molecular and cellular improvements translated into functional recovery as high-dose ABPS treatment restored renal function to near-normal levels, including a 58.1% reduction in BUN, a 34.5% reduction in Scr, a 23.6% reduction in NGAL, a 29.6% reduction in KIM-1, and a 32.2% reduction in CysC. Hematoxylin and eosin (H&E) and periodic acid–Schiff (PAS) staining and quantitative scoring analysis of kidney injury revealed severe tubular necrosis and glomerular damage in rats in the hypoxia group, which were significantly attenuated in both the ABPL and ABPH groups (p < 0.05).ConclusionABPS mitigates hypoxic renal injury by reducing NETs and synergistically regulating oxidative stress. ABPS shows potential as a multi-target, low-toxicity candidate for renal protection.